2020
DOI: 10.31219/osf.io/gmuzk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

State of the Art Survey of Deep Learning and Machine Learning Models for Smart Cities and Urban Sustainability

Abstract: Deep learning (DL) and machine learning (ML) methods have recently contributed to the advancement of models in the various aspects of prediction, planning, and uncertainty analysis of smart cities and urban development. This paper presents the state of the art of DL and ML methods used in this realm. Through a novel taxonomy, the advances in model development and new application domains in urban sustainability and smart cities are presented. Findings reveal that five DL and ML methods have been most applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Generative Adversarial Networks (GAN) have been utilized for simulating urban patterns [38,39]. Contributions from deep learning (DL) and machine learning (ML) methods to the evolution of models in various aspects of prediction, planning, and uncertainty analysis in smart cities and urban development have been notable [40,41], providing support for urban planning and decision making [42].…”
Section: Application Of Machine Learning In Urban Perceptionmentioning
confidence: 99%
“…Generative Adversarial Networks (GAN) have been utilized for simulating urban patterns [38,39]. Contributions from deep learning (DL) and machine learning (ML) methods to the evolution of models in various aspects of prediction, planning, and uncertainty analysis in smart cities and urban development have been notable [40,41], providing support for urban planning and decision making [42].…”
Section: Application Of Machine Learning In Urban Perceptionmentioning
confidence: 99%
“…At the same time, advances in computer science theory, mathematical research, and processing power equip us with the tools we need to gather the data (Milojevic-Dupont and Creutzig, 2021). New technologies and their applications have shown to be extremely advantageous in terms of fostering a better future in dealing with the challenges of future cities (Nosratabadi et al, 2019). Artificial intelligence applications such as machine learning (ML) have become increasingly popular in recent years as a versatile tool for technological advancement (Rolnick et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning techniques have contributed to a variety of application fields, such as transportation management, urban planning, distribution of resources, forecasting energy requirements, forecasting food security and supply, and monitoring as well as forecasting poor air quality, etc. (Audu et al, 2020; Nosratabadi et al, 2019; Wataya and Shaw, 2019). Given that the climate change issue is extremely complex and necessitates multidisciplinary research (Huntingford et al, 2019), the usage of ML techniques has shown to be a helpful tool for realizing and predicting climate-related issues (Koc and Acar 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other existing surveys have explored the different applications of Deep RL, e.g. in healthcare (Yu et al, 2019), communications/networking (Luong et al, 2019), video games (Justesen et al, 2019;Skinner & Walmsley, 2019), cyber security (Nguyen & Reddi, 2019), natural language processing (Whiteson, 2019;Stylianou & Vlahavas, 2019), robotics (Tai et al, 2016), biology (Mahmud et al, 2018), urban sustainability/transportation (Nosratabadi et al, 2020), agriculture (Yang & Sun, 2019), and many others (Li, 2019).…”
Section: Introductionmentioning
confidence: 99%